Preclinical research in paclitaxel-induced neuropathic pain: a systematic review - Bacalhau, Carolina; Costa-Pereira, José Tiago; Tavares, Isaura (Frontiers in Veterinary Science, 2023)
Chemotherapy-induced peripheral neuropathy (CIPN) is a common consequence of cancer treatment and pain is a frequent complaint of the patients. Paclitaxel, a cytostatic drug, generates a well-described peripheral nerve injury and neuroinflammation, which may be experimentally mimicked in animal models. We conducted a systematic review analyzing the experimental design, reporting and mechanisms underlying paclitaxel-induced neuropathy in the included studies to establish the perspectives of translation of the current literature in models of CIPN. We elected studies published in Pubmed and Scopus between 1 January 2018 and 3 December 2022. According to a defined mesh of keywords searched, and after applying exclusion and inclusion criteria, 70 original studies were included and analyzed in detail. Most studies used male Sprague-Dawley rats to induce paclitaxel-induced neuropathy, used low doses of paclitaxel, and the analyzed studies mainly focused at 14-28 days of CIPN. Mechanical nociceptive tests were preferred in the behavioral evaluation. The mechanisms under study were mainly neuroinflammation of peripheral nerves. The overall methodological quality was considered moderate, and the risk of bias was unclear. Despite the ample preclinical research in paclitaxel-induced neuropathy, this systematic review alerts to some flaws in the experimental design along with limitations in reporting, e.g., lack of representation of both sexes in experimental work and the lack of reporting of the ARRIVE guidelines. This may limit the reproducibility of preclinical studies in CIPN. In addition, the clinical features of CIPN should be considered when designing animal experiments, such as sex and age of the CIPN patients. In this way the experimental studies aiming to establish the mechanisms of CIPN may allow the development of new drugs to treat CIPN and translation in the research of CIPN could be improved.